Humility in Seminary Student Formation: A Mixed Method Community Action Study - Captari, Laura E. (Journal of spiritual formation & soul care, 2021)
This cross-sectional mixed method community action study exploring the virtue of humility was conducted as part of a collaborative practical theology project at a pluralistic, ecumenical Mainline Protestant seminary. Students (N = 65) in a spiritual formation graduate class completed quantitative measures of humility, spiritual well-being, differentiation of self (DoS), mentalization, and mindfulness, while open-ended qualitative data captured their perspectives about the role of humility in formation. Qualitative results revealed important nuances about emerging religious leaders’ views on humility, including experiencing this virtue as (a) facilitative to their vocational growth (e.g., promoting learning, self-understanding, relational connections, and deeper spirituality), (b) challenging (e.g., self-deprecating, unnecessary, and contrary to ministry), or (c) some combination of both. Quantitative results documented positive associations between relational capacities (e.g., DoS, mentalization) and humility, and these links were mediated by mindful awareness. Implications for measuring and promoting holistic spiritual development among emerging religious leaders are discussed.